Forest filter effect for polybrominated diphenyl ethers in a tropical watershed. (15th October 2019) - Barrett, Kayon S.C.; Jaward, Foday M.; Stuart, Amy L.
Abstract: There is limited research characterizing the fates of persistent organic pollutants in tropical multi-use watersheds. This study aimed to evaluate the role of forests in the environmental fates of select polybrominated diphenyl ethers (PBDEs) for a case study tropical drainage basin, the Rio Cobre watershed. Field samples of deposition, soil, litterfall and the atmosphere of a forest and nearby clearing were analyzed for the presence of the PBDEs (PBDE-28, 47, 99, 100, 153, 154, 183 and 209), which are routinely detected in the environment. The mean air and litterfall concentrations of these PBDEs were generally lower in the forest than in the clearing, whereas the deposition flux rate and soil concentrations were higher in the forest. The results suggest that the forest filtered the PBDEs by transferring them from the atmosphere to the soil, despite the tropical nature of the study site. Highlights: Polybrominated diphenyl ethers were measured in a tropical forest and nearby clearing. Air concentrations were lower in the forest than clearing. Bulk depositions were generally greater in the forest than clearing. Soil concentrations were higher in the forest than clearing. Tropical forests appear to filter polybrominated diphenyl ethers.